ECOLOGICAL EDUCATION PROGRAMS IN MODERN IRELAND: EXPERIENCE FOR UKRAINE - Marusynets, Marianna (Mountain School of Ukrainian Carpaty, 2024)
This article addresses the critical issue of ecology and environmental education within the framework of modern global challenges, emphasizing the urgency of fostering environmental literacy and high moral values among the younger generation. Through a retrospective and reflexive-analytical review of scientific sources, the study explores the conceptual framework and methodological approaches of environmental education in Ukrainian and Irish contexts. Ukrainian research highlights the need for systematic integration of ecological principles across all levels of education, combining rational and emotional dimensions of human interaction with nature to promote sustainable development and environmental consciousness. In contrast, Irish practices focus on innovative technologies and strategic state programs such as «Fit for 55» and the «Green Deal», positioning Ireland among the global leaders in environmental protection. The study highlights key trends, including the prioritization of environmental education in national policies, integration into school curricula, and the development of emotional and intellectual engagement with nature starting from early childhood. Notable programs such as Green Schools emphasize hands-on learning and practical applications, instilling responsibility for resource management and waste reduction in students and fostering a culture of sustainability. Moreover, the article underscores the role of outdoor learning in enhancing creativity, speech development, and overall well-being, aligning with Irish educational strategies. However, challenges persist, including gaps in social research on environmental education and debates over the balance between utilitarian and empathetic approaches to ecological learning. By examining these issues, the article contributes to the discourse on global environmental education and offers valuable insights for fostering a holistic environmental culture.